Beginning CSharp 2005 Databases - Huddleston, James (Apress, 2012)
Every program manipulates data. Most real-world programs use data stored in relational databases, so every C# programmer needs to know how to access relational data. This book explains how to do this in C#, with ADO.NET and Language-Integrated Query (LINQ), against SQL Server 2005. The same principles and techniques apply to C# programming against other relational database management systems, such as DB2, MySQL, Oracle, and PostgreSQL, so what you learn here is valuable whatever database you use.